Contribution of SNP arrays in diagnosis of deletion 2p11.2-p12. - Rocca, Maria Santa; Fabretto, Antonella; Faletra, Flavio; Carlet, Ombretta; Skabar, Aldo; Gasparini, Paolo; Pecile, Vanna (Gene, 2012)
Deletions of the short arm of chromosome 2 are exceedingly rare, having been reported in few patients. Furthermore most cases with deletion in 2p11.2-p12 have been studied using standard karyotype and so it is not possible to delineate the precise size of deletions. Here, we describe a 9-year-old girl with a 9.4 Mb de novo interstitial deletion of region 2p11.2-p12 identified by SNP array analysis. The deleted region encompasses over 40 known genes, including LRRTM1, CTNNA2 and REEP1, haploinsufficiency of which could explain some clinical features of this patient such as mental retardation, speech delay and gait abnormalities. A comparison of our case with previously reported patients who present deletions in 2p11.2-p12 was carried out. Our case adds new information to the deletion of 2p11.2-p12, improving the knowledge on this rearrangement.
Keywords: Abnormalities, Multiple; Child; Chromosomes, Human, Pair 2; Female; Humans; Intellectual Disability; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Sequence Deletion